1. ## formula explanation

Can you please tell me in dummy terms what is going on with the GCF parts in this equation and how -2HW got moved to the right side of the equation. Was that part of the GCF or was it just subtracted from both sides of the equation?

thanks

S=2LW+2LH+2WH

Since L is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation.
2LW+2LH+2WH=S

Factor out the GCF of 2L from each term in the polynomial.
2L(W)+2L(H)=-2HW+S

Factor out the GCF of 2L from 2LW+2HL.
2L(W+H)=-2HW+S

Divide each term in the equation by (W+H).
(2L(W+H))/(W+H)=-(2HW)/(W+H)+(S)/(W+H)

Simplify the left-hand side of the equation by canceling the common terms.
2L=-(2HW)/(W+H)+(S)/(W+H)

Simplify the right-hand side of the equation by simplifying each term.
2L=(-2HW+S)/(W+H)

Divide each term in the equation by 2.
(2L)/(2)=(-2HW+S)/(W+H)/(2)

Simplify the left-hand side of the equation by canceling the common terms.
L=(-2HW+S)/(W+H)/(2)

Simplify the right-hand side of the equation by simplifying each term.
L=(-2HW+S)/(2(W+H))

2. Which part exactly are you not sure of?

3. Originally Posted by hansfordmc
S = 2LW + 2LH + 2WH
Don't know what you're asking...or why all that work is shown...
If you're solving that equation for L, then:

1: get L terms on one side: 2WL + 2HL = S - 2WH

2: factor left side: L(2W + 2H) = S - 2WH

3: divide by 2W + 2H : L = (S - 2WH) / (2W + 2H) ; finished.